given ylnydx+(x-lny) dy=0
rArr(dx)/(dy)=(lny-x)/(ylny)
(dx)/(dy)=1/y -x/(ylny)
(dx)/(dy) +(1/(ylny))x=1/y ......(1)
this is a linear differential equation of the form ((dx)/(dy) +P*x=Q) , where P and Q are either constant or a function of 'y'
So integrating factor is e^(intPdy), and here P = (1/(ylny)) , Q =1/y
multiply equation (1) by e^(intPdy), we get
e^(intPdy)(dx)/(dy) +Pxe^(intPdy)=Qe^(intPdy)
rArr d(xe^(intPdy))/(dy)=Qe^(intPdy)
rArrd(xe^(intPdy))=Qe^(intPdy)dy
integrating both sides
intd(xe^(intPdy))=intQe^(intPdy)dy
xe^(intPdy)=intQe^(intPdy)dy
substitute P and Q in the above equation
xe^(int(1/(ylny))dy)=int1/ye^(int(1/(ylny))dy)dy+c. ...(2)
to solve the integrating factor, put lny=trArr (1/y)dy=dt
rArr e^(int(1/(ylny))dy)=e^(int(1/tdt) = e^lnt = t = lny
so from (2)
xlny=int1/ylny dy+c.
to solve R.H.S, using same substitution, you get int1/ylnydy=((lny)^2)/2
rArr xlny=((lny)^2)/2+c.
rArr2xlny=(lny)^2+k, k=2c.
rArr (lny)^2-2xlny+k=0
rArr lny={2x+-sqrt(4x^2-4k)}/2...[because," the quadr. forml.]"
:. lny=x+-sqrt(x^2-k).
:. y=e^(x+-sqrt(x^2-k))," is the Gen. Soln."
for particular solution, assuming constant c = 0,we get
y=e^(x+-sqrt(x^2-0)) rArry=e^(2x) rArr2x=lny"